Analisis faktor-faktor yang berhubungan dengan kejadian abortus pada karyawati - Yekti Satriyandari (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2016)
Abstract: This research aims to see a model of the provision ofbreastfeeding exclusively on an employee in Institute of Health Science‘aisyiyah. A method of research is qualitative approach (in-depthinterview) that stress to non numerical analysis and analysis on theinterpretative social phenomena ..The validity of the data with the techniqueof triangulation .Processing and analysis of data using a method of colaizzi.The results of research shows a model of granting exclusive breastfeedingemployee stikes aisyiyah in by squeezing breastfeeding and the provisionof breastfeeding when abandoned by working with using a spoon orteat. The benefits of granting exclusive breastfeeding is the baby immune.Suggested that Stikes Aisyiyah can improve facilities and infrastructureand providing a special room breastfeeding corner.